A Case Delayed Hemorrhage from the Stump of the Superior Rectal Artery after Abdominoperineal Resection of the Rectum - Yuichi Sanada; Kenichi Nonaka; Takao Takahashi; Yoshihiro Tanaka; Shinji Osada; Kazuhiro Yoshida (Case Reports in Medicine)
A 66-year-old man underwent abdominoperineal resection for advanced rectal cancer. On day 3 post surgery, a decompression tube was placed for postoperative ileus. Symptoms associated with ileus immediately disappeared. On day 7 post surgery, the patient vomited large amounts of fresh blood and became hemodynamically unstable. An emergency angiography revealed active bleeding from the stump of the superior rectal artery communicating with the third portion of the duodenum. Complete obliteration of the stump by proximal coil embolization was performed to achieve successful hemostasis. The postclinical course was uneventful and the patient was discharged on day 40 post surgery.